Mutual Fund Investment: Investment Alternatives for Beginner Investors - Maisaroh, Neng; Adelia, Vernica Ayu; Fuadi, Fatih (Airlangga Journal of Innovation Management, 2025)
This study aims to observe the phenomena related to mutual fund investment as an alternative investment for beginner investors in Indonesia. It employs a post-positivism model of Systematic Literature Review (SLR), with data gathered from the Scopus website. A total of 36 documents from previous studies, published between 1975 and 2025, were analyzed. The findings reveal that mutual fund investment is a popular choice for inexperienced investors seeking to minimize risks commonly associated with direct investment in the capital market. Mutual funds offer several benefits, including professional fund management, portfolio diversification, transparency of information, high liquidity, low transaction costs, and generally lower risk compared to direct stock investments. In addition, rapid technological advancements have led to the emergence of digital platforms and applications that simplify the process of investing in mutual funds. These innovations enhance user accessibility and convenience, making it easier for new investors to participate in the capital market. The implication of this research is to provide better insight into the strengths and weaknesses of each investment platform or application, thereby assisting novice investors in making more informed and strategic investment decisions. Ultimately, this can help them to achieve their financial goals more effectively while minimizing potential losses.